The Illusion of Ideological Antagonism? Reassessing The Relationship between Communism, Capitalism, and Transnational Power - Sreoshi Sinha (Pena Kreatif Publisher, 2026)
This article examined the conventional assumption that communism and capitalism developed as fundamentally antagonistic systems. It investigated recurring historical claims that influential financial, banking, and political actors interacted with, facilitated, or benefited from revolutionary socialist movements despite apparent ideological opposition. Using a qualitative historical-analytical approach, the study drew upon the writings of Karl Marx, Friedrich Engels, and Mikhail Bakunin, elite theory, and selected historical debates concerning finance and revolution, with particular attention to the Bolshevik Revolution. The analysis found that ideological conflict alone did not adequately explain historical interactions between revolutionary socialism and influential financial interests. Instead, patterns of political, economic, and institutional centralization emerged as a recurring theme across competing interpretations. The study concluded that the relationship between communism, capitalism, and power was more complex and interconnected than conventional narratives generally suggest.